Improving junior high school students’ listening comprehension in English learning Spotify podcast application - Andien Laksita Syafitri; Ririn Ambarini; Fitri Yulianti (English Learning Innovation, 2026)
Listening comprehension remains a pervasive challenge for junior high school students’, primarily due to rigid classroom intructional media that often induce high text anxiety and cognitive overload. This study investigated the empirical effectiveness of intergrating the Spotify application to improve students’ listening comprehension within an English language learning framework. Utilizing a quasi-experimental approach, data were gathered from a final sample of  junior high school students split into an experimental group and control group. Data were analyzed using Analysis of Covariance (ANCOVA) in IBM SPSS to neutralize initial baseline differencess by treating pre-test score a covarite. The descriptive findings revealed that before the intervention, students’ listening comprehension in both groups resided at a low-to moderate level. Following the instructional cycle, the experimental group achieved a high level of proficiency, marking a substantial and positive upward shift in their ability to decode Spoken English text. The inferential ANCOVA result confirmed that  the data revealed a clear difference in how the two performed on the post-test listening , with the model closely matches the reality of data exceptionally well . These findings suggest that the user-centric control of Spotify, such as adjustable playback speeds, act a vital cognitive scaffold that lowers student’s affective filters and anxiety. Ultimately, this study provides a practical blueprint for languange educators aiming to foster autonomous and resilent English listening in the digital era.